Export versus FDI in services - Bhattacharya, Rudrani; Patnaik, Ila; Shah, Ajay; International Monetary Fund ([Washington, D.C.] : International Monetary Fund, 2010)
In the literature on exports and investment, most productive firms are seen to invest abroad. In the Helpman et al. (2004) model, costs of transportation play a critical role in the decision about whether to serve foreign customers by exporting, or by producing abroad. We consider the case of tradable services, where the marginal cost of transport is near zero. We argue that in the purchase of services, buyers face uncertainty about product quality, especially when production is located far away. Firm optimisation then leads less productive firms to self-select themselves for FDI. We test this prediction with data from the Indian software industry and find support for it.
Cover Page; Title Page; Copyright Page; Contents; 1 Introduction; 2 How services producers serve foreign customers; 3 Testing this prediction; 3.1 The Indian software industry; 3.2 The data; 3.2.1 The chemicals dataset; 3.2.2 The software services dataset; 3.3 Measuring Productivity; 4 Results; 4.1 Chemicals; 4.2 Software Services; 5 Conclusions; Footnotes.
Includes bibliographical references.
Keywords: Investments, Foreign -- India -- Econometric models; Exports -- India -- Econometric models; Industrial productivity -- India -- Econometric models; Computer service industry -- India -- Econometric models; Investissements étrangers -- Inde -- Modèles économétriques.; Exportations -- Inde -- Modèles économétriques.; Productivité -- Inde -- Modèles économétriques.; Services informatiques -- Inde -- Modèles économétriques.; Exports -- Econometric models; Industrial productivity -- Econometric models; Investments, Foreign -- Econometric models; India; Electronic books